2007
DOI: 10.1152/jn.01179.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of μ-Opioid Receptor Modulation on GABAB Receptor Synaptic Function in Hippocampal CA1

Abstract: McQuiston AR. Effects of -opioid receptor modulation on GABA B receptor synaptic function in hippocampal CA1. J Neurophysiol 97: 2301-2311, 2007. First published January 10, 2007 doi:10.1152/jn.01179.2006. Activation of -opioid receptors (MORs) alters information coding, synaptic plasticity, and spatial memory in hippocampal CA1. In CA1, MORs act by inhibiting GABA release onto both GABA A and GABA B receptors exclusively. MOR activation can facilitate excitatory inputs in CA1 dendritic layers by inhibiting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 46 publications
3
31
0
1
Order By: Relevance
“…Previous studies have suggested that MOR activation can influence excitatory activity in all layers of hippocampal CA1 (McQuiston and Saggau, 2003;McQuiston, 2007). However, the relative effectiveness of MOR activation in the discrete layers of CA1 is not fully understood.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have suggested that MOR activation can influence excitatory activity in all layers of hippocampal CA1 (McQuiston and Saggau, 2003;McQuiston, 2007). However, the relative effectiveness of MOR activation in the discrete layers of CA1 is not fully understood.…”
Section: Resultsmentioning
confidence: 98%
“…However, a physiological study reported that less than half of interneurons projecting to the proximal apical dendrites in SR were hyperpolarized by MOR activation (Svoboda et al, 1999). Yet other physiological studies have shown that MOR activation can significantly increase the amplitude of excitatory inputs in SR (McQuiston and Saggau, 2003;McQuiston, 2007). To examine the effect of MOR activity on excitatory inputs in SR, SR was isolated from SP by a razor cut between SP and SR (Fig.…”
Section: Mor Activation Increases the Epsp In Isolated Srmentioning
confidence: 99%
See 2 more Smart Citations
“…At 4 weeks following cell injection, rat brain slices were prepared as described previously (McQuiston, 2007). Briefly, the rats were deeply anesthetized with ketamine (200 mg/kg) and xylazine (20 mg/kg), transcardially perfused with ice-cold buffer (consisting of in mM: sucrose 230, KCl 2.5, CaCl 1, MgCl 2 4, NaHPO 4 1, NaHCO 3 25, and glucose 25) and sacrificed by decapitation.…”
Section: Electrophysiological Studiesmentioning
confidence: 99%